Justice and home affairs: impact of the European Union on the internal security of Turkey - Bakar, Ayhan (2011)
This research project focuses on the impact of the EU's internal security policy on Turkey during its accession process. It investigates the conditions that determine the EU's success in effecting the changes in the internal security of Turkey. In order to limit the field of Justice and Home Affairs, the study selects the fight against Organised Crime, Terrorism and Drugs as its case studies. It takes Turkey's application for EU membership in 1987 as the starting point of the analysis and concludes in 2010. It tracks domestic change in Turkey by considering the adoption of the EU acquis, the development of its administrative capacity and the extent of internal security cooperation with the EU. The research aims to provide insight into the way the EU operates the external dimension of JHA towards applicant states, the conditions under what it exerts through influence of JHA, and the extent to which the EU shapes the internal security of Turkey during the enlargement process.